LOCAL EFFECT OF GLOBAL WARMING IN THE RIVNE REGION AND ITS IMPACT ON THE FUNCTIONING OF WATER ECOSYSTEMS - Kurylіuk O.; Klymenko, Mykola; Statnуk Ihor (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
Water resources are characterized by the greatest vulnerability to climate change and are extremely important as a factor for the rise and development of any biological and human activity. The increasing temps of the global warming process and dynamics of climate change in recent decades has caused the relevance of the selected research area. The local effects of global warming were investigated for the territory of Rivne region, during the period 1945–2017, which is of the great interest to scientists in terms of climate shifts. An overview of academic literature related to climate change in Ukraine was undertaken to achieve the intended goal. Monthly temperature and precipitation data from meteorological stations within Rivne region were obtained for the study period 1945–2017 to specify the local climate changes. The study indentified that the time period 1990–2015 was the period of maximum monthly temperatures. The period of rapid temperature increase in the study territory began in the 1990’s. Analysis of rainfall data indicated that the frequency of abnormal rainfall has increased since 1992 and the redistribution of rainfall during the year was determined. As a result, this study enabled to form the basis for further investigation of changes in the state of water ecosystems on the backdrop of climate change.